Pluralisme Hukum dalam Penyelesaian Kekerasan Anak: Kearifan Lokal dan Sistem Peradilan Pidana di Kota Jayapura - Budiyanto Budiyanto; Abdul Malik Mufty; Dian Rahadian (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
Child violence cases in Jayapura City demonstrate a distinctive pattern of legal settlement characterised by the strong coexistence of customary law and the formal juvenile criminal justice system. While national legislation mandates diversion and restorative justice as primary mechanisms in handling children in conflict with the law, empirical findings reveal that most cases are resolved through indigenous customary forums known as para-para adat. This study aims to analyse the forms of settlement applied to child violence cases and to identify the constraints encountered in implementing both customary mechanisms and the formal juvenile justice system. The research employs a normative-empirical approach by combining statutory analysis with field data obtained from law enforcement institutions, legal aid organisations, and community respondents. The findings indicate that approximately ninety percent of cases between 2019 and 2024 were settled through customary mechanisms involving collective responsibility and the payment of customary fines as symbolic and material restoration. Diversion mechanisms under the formal system were rarely implemented. Although customary settlement is perceived as flexible, culturally legitimate, and socially restorative, several obstacles persist, including disagreement over compensation, inability to fulfil customary obligations, and limited awareness of restorative justice procedures. The study highlights the need to harmonise legal pluralism within child protection policies to ensure that customary practices align with the best interests of the child and national legal standards.